The Correlation between Lecturers’ Interpersonal Communication and Students’ Learning Motivation - Hamdan, Ahmad; Attika, Shidratul (Academia Publication, 2024)
Communication is used in everyday life to interact with other individuals. Establishing good communication aims to create good social conditions as well. This study aimed to determine the correlation between lecturers’ interpersonal communication and students’ learning motivation. This study was conducted using a non-experimental quantitative approach with correlational study methods. The questionnaires were developed from DeVito’s interpersonal communication theory and Pintrich & Groot’s learning motivation theory. . The respondents in this study were 36 students of the STAIN Sultan Abdurrahman Islamic Broadcasting Communication Study Program, Riau Islands. Based on the results of the correlation test, the 2-tailed Sig value was 0.003 <0.005, it can be concluded that there was a correlation between lecturers’ interpersonal communication and students’ learning motivation. This study was the first to be conducted at STAIN Sultan Abdurrahman as a tertiary education institution with a focus on effective interpersonal communication built by lecturers with students as a first step in creating a good academic atmosphere and encouraging all components of student learning motivation to achieve good academic achievement.